PENGARUH EDUKASI KESEHATAN REPRODUKSI PADA REMAJA PUTRI TERHADAP PENGETAHUAN TENTANG PERSONAL HYGIENE KETIKA MENSTRUASI DI JURUSAN KEBIDANAN UNIVERSITAS SARI MULIA - Amalia Fatimah, Rizqina; Zulliati; M. Fajriannoor TM (Midwifery And Complementary Care, 2022)
Background: Female adolescent are at higher risk of reproductive organ infections. One of the causes of reproductive tract infections is improper hygiene behavior. A potential solution is providing reproductive health education on personal hygiene during menstruation to improve knowledge. Objective: To identify the influence of reproductive health education on adolescent girls’ knowledge of personal hygiene during menstruation in the Midwifery Department of Sari Mulia University. Method: This research used a pre-experimental method with a one-group pretest-posttest design. The sampling technique was purposive sampling, with samples selected based on research criteria. A total of 30 midwifery students participated. Data analysis was conducted using the marginal homogeneity test. Results: In the pretest, 10 participants (33.3%) were categorized as having good knowledge, 10 (33.3%) as moderate, and 10 (33.3%) as poor. In the posttest, 24 participants (80.0%) were categorized as having good knowledge, and 6 (20.0%) as moderate. The marginal homogeneity test showed a p-value of 0.0001 (p < 0.05), indicating a significant difference between variables. Conclusion: There is a significant influence of reproductive health education on adolescent girls’ knowledge of personal hygiene during menstruation in the Midwifery Department of Sari Mulia University. Keywords: Education, Personal Hygiene, Adolescents